The role of teacher self-efficacy on the instructional quality in 21st century: A study on vocational teachers, Indonesia - Nur Kholifah; Muqarramah Sulaiman Kurdi; Muhammad Nurtanto; Farid Mutohhari; Moh Fawaid; Tamil Selvan Subramaniam (Institute of Advanced Engineering and Science, 2023)
The quality of learning for vocational teachers in Indonesia in the 21st century is still a very serious problem and has not yet received a practical solution. The prediction is that the self-efficacy of vocational teachers is weak and is motivated by very limited mastery of digital technology and low psychological well-being, which is strongly suspected as a contributing factor. This study examines the role of self-efficacy and mediation of digital technology intimacy and psychological well-being in improving the quality of vocational teacher learning. This research is an ex-post-facto study with 216 vocational teachers as respondents. Data was collected using a questionnaire technique consisting of digital technology intimacy (DTI), psychological well-being (PWB), self-efficacy (SE), and instructional quality (IQ) questionnaires using four Likert scales, namely strongly agree to strongly disagree. Data were analyzed using structural equation modeling (SEM) analysis techniques with path analysis and bootstrap methods. The results of the study revealed that SE had a significant and positive effect on DTI and PWB in influencing the quality of learning. On the other hand, DTI and PWB have a positive effect on self-efficacy and learning quality.